MITIGASI DAN STRATEGI INDONESIA DALAM MENGHADAPI TARIF TRUMP JILID KEDUA - Miftahudin, Erwin; Kalam, Rizalul; Abdurrahman, Muhammad Hanif (Department of International Relations Universitas Satya Negara Indonesia, 2025)
In the contemporary era, economic power has become a key pillar in determining a country’s strategic position within the global political order. International trade is now facing serious challenges due to the implementation of protectionist policies by the United States (US) under the second term of President Donald Trump. The US has imposed high tariffs on several of its trading partners, including Indonesia. This phenomenon reflects a significant shift in US economic policy, which now leans more toward neo-mercantilism. As a result, Indonesia faces several major risks, including declining competitiveness, export levels, investment flows, a potential wave of layoffs, and economic slowdown. This study analyzes the impact of the US’s second wave of protectionism, particularly on Indonesia’s manufacturing industry, from the perspective of international political economy using a qualitative approach. Furthermore, the study evaluates strategic measures that the Indonesian government can adopt, including renegotiation with the US, expansion into non-traditional markets, and strengthening national competitiveness. The findings of this study are expected to serve as a reference for the government in formulating resilient and adaptive strategies in response to the dynamics of global protectionism.